Design of Torsion Plate Energy-Absorbing Member and Analysis of Energy-Absorbing and Anti-Impact Characteristics - Zhang, Jianzhuo; Guo, Hao; Xiao, Yonghui; Pan, Yishan; Jiang, Biao; Su, Shijie; Ni, Baojun (Shock and Vibration, 2023)
In order to effectively improve the impact resistance performance of the roadway anti-impact hydraulic support and reduce the loss caused by rock burst to a certain extent, a torsion plate energy-absorbing member was designed for using with the hydraulic column. By using theoretical analysis and numerical simulation methods and combining them with the parameters of the energy-absorbing characteristics evaluation index, single-factor tests were designed. Under the premise of constant impact velocity, the influence law of torsion angle, plate thickness, and fillet radius of the pressure plate on the energy-absorbing and anti-impact characteristics of energy-absorbing members were analysed. The results show that the deformation process and resistance trend of the torsion plate correspond to energy absorption. The resistance stability is high in the reaction force platform stage, and the energy increases linearly. With the increase of the torsion angle, the mean value of the reaction force increases, the fluctuation of the reaction force platform stage becomes more obvious, the specific energy absorption increases linearly, and the standard deviation reaches the minimum at 480°. Both the tensile length and the length of the reaction force platform stage increase continuously. With the increase of the plate thickness, the flatness of the torsion plate shows a trend of bad-good-bad, the mean value of the reaction force gradually increases, the specific energy absorption grows faster and then slower, and the tensile length and the length of the reaction force platform stage increase accordingly. With the increase of the fillet radius, the flatness of the torsion plate is better and the reaction force has a small improvement. The fluctuation of reaction force is most significant when the fillet radius is 2 mm, and the energy-absorbing member has the largest swing. The specific energy absorption is highest when the fillet radius is 2.5 mm, the standard deviation shows a tendency to develop firstly decreasing and then stabilising, the tensile length of the torsion plate decreases slightly, and the length of the reaction force platform firstly increases and then tends to stabilise. The torsion plate energy-absorbing member is a more ideal energy-absorbing and anti-impact member, which plays a positive role in the energy-absorbing and anti-impact of the hydraulic support.